Pengaruh CAMEL terhadap profitabilitas bank umum syariah periode 2019-2022 - Sophianita, Amelia; Paramita, R.A. Sista (Jurnal Ilmu Manajemen, 2024)
This research aims to determine the results of the analysis of the influence of CAMEL (Capital, Asset Quality, Management, Earnings, and Liquidity) on profitability in Islamic commercial banks for the period 2019-2022. In this research, Capital is proxied by the Capital Adequacy Ratio (CAR), Asset quality is proxied by Non-Performing Financing (NPF), Management is proxied by Net Operating Margin (NOM), Revenue is proxied by earnings efficiency (BOPO), Liquidity is proxied by Financing to Deposit Ratio (FDR) and Profitability is proxied by Return on Assets (ROA). The object of this research is 10 Islamic commercial banks with data collection techniques using purposive sampling. This type of research is causal associative with a quantitative approach which is processed using multiple linear regression analysis techniques on IBM SPSS tools version 27 software. The results of the research state that the NOM and BOPO variables have a significant positive effect on ROA, while other independent variables such as CAR, NPF, and FDR does not have a significant influence on ROA. The implications of the research findings indicate that management efficiency (NOM) and earnings efficiency (BOPO) are crucial for the profitability (ROA) of Islamic commercial banks. Therefore, banks need to enhance their operational and management efficiency to improve profitability.